Development of a Routes Guide Innovation for Historical, Cultural and Natural Resources U-thong District, Suphanburi Province - Wisutruangdat, Wittaya (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research has develo a routes guide innovation for historical, cultural and natural resources U-thong district, Suphanburi Province. This research used quantitative research, and the research tools were questionnaires. Quantitative research had 2 steps. 1) Checked the validity of innovation a routes guide for historical, cultural and natural resources U-thong district, Suphanburi Province by the expects 9 key informants. Data were selected by using purposive sampling. 2) Checked complacency of innovation a routes guide by tourists visited tourist attractions 385 peoples. Used data selection method by multistage random sampling. Data was analyzed by mean and standard deviation. Results indicated that 1) the experts have had the appropriateness of content has been most appropriate at the highest level especially contents in the book have been easy to understand with the most suitable level. The appropriateness of photo arrangement appropriateness has been the least because some picture has been blurry. 2) The overall for complacency of innovation a routes guide was high level (x ̅ = 4.29, S.D. = 0.53). The highest complacency was benefits and values was at high level (x ̅ = 4.41, S.D. = 0.47). The lowest complacency was Language and it was at high level (x ̅ = 4.23, S.D. = 0.59). Suggestion of this study were 1) there should be other innovations, and to strengthen tourism in U-thong district, and 2) should have travel routes for the elderly to come to travel in U-thong district.